Functional Decentralization Construct in Decentralization Policy in Indonesia (A Study of Irrigation, Education, and Free Trade Sectors) - Alma Arif; Irfan Ridwan Maksum (Magister Administrasi Publik, 2017)
This research analyze the practice of irrigation, education, and free trade governance linked with functional decentralization concept in Indonesia’s decentralization policy frame. This research use constructivist approach and qualitative-descriptive method. Research result find several factors that cause functional decentralization in Indonesia’s decentralization policy for irrigation, education, and free trade is not adopted. Political institution is not adopted, independence of the farmers, integration of river and irrigation web, and state constitution, are the factors from irrigation side. Several factors in education are the existence of educational boards, the independence of school, devolution in education governance, and state constitution. For free trade, the institution of Batam governance, members structure in Batam’s boards, the uncertainty of BP. Batam in Indonesia’s administration structure, and state constitution, which make functional decentralization is not adopted. Generally, state constitution is major factor of functional decentralization is not adopted. The Construction of Decentralization in the Future of Indonesia’s Decentralization Policy especially in irrigation, education, and free trade can be done gradually begin from inter-local government cooperation, state-local collaboration in boards until establishing the functional decentralization’s organization.